PENGARUH MODEL PEMBELAJARAN MASTER TERHADAP LITERASI MATEMATIS DITINJAU DARI PERBEDAAN GENDER - Ani Sopiani Martinah; Okta Hari Kharisma; Sri Purwanti Nasution; Agus Pahrudin (Universitas Nahdlatul Ulama Sunan Giri Bojonegoro, 2019)
This study aims to determine the effect of MASTER learning models (Motivating, Acquiring, Searching, Triggering, Exhibiting, and Reflecting) on ​​mathematical literacy in terms of gender differences. The method used in this study is Quasy Experimental Design. A random sampling technique took a sample of 60 students. Data collection is carried out with written tests and documentation. The method uses an analysis of variance (ANOVA). Hypothesis testing uses two different path tests of variance analysis in cells. The results showed that there were mixed effects of each learning model on students' mathematical literacy abilities. There was no influence between female and male gender on students' mathematical literacy abilities. There was no interaction between learning models and gender differences in students' mathematical literacy abilities. The teacher must strive to improve the mathematical literacy skills of middle school students so that students are more motivated to learn. Penelitian ini bertujuan untuk mengetahui pengaruh model pembelajaran MASTER (Motivating, Acquiring, Searching, Triggering, Exhibiting, and Reflecting)terhadap literasi matematis ditinjau dari perbedaan gender. Metode yang digunakan dalam penelitian ini adalah Quasy Experimental Design. Sampel sebanyak 60 siswa yang diambil dengan teknik random sampling. Pengumpulan data dilaksanakan dengan tes tertulis dan dokumentasi. Teknik analisis data menggunakan analisis variansi (ANOVA). Uji hipotesis menggunakan uji analisis variansi dua jalan sel tak sama. Hasil penelitian menunjukanterdapat pengaruh yang berbeda antara masing-masing model pembelajaran terhadap kemampuan literasi matematis peserta didik. Tidak terdapat pengaruh antara gender perempuan dan laki-laki terhadap kemampuan literasi matematis peserta didik. Tidak terdapat interaksi antara model pembelajaran dan perbedaan gender terhadap kemampuan literasi matematis peserta didik. Untuk meningkatkan kemampuan literasi matematis peserta didik SMP, pendidik harus berupaya agar peserta didik lebih termotivasi untuk belajar.